Near-dry deep hole drilling with BTA tool (On the boring into aluminum alloy and steel with prepared hole) - Koji AKASHI; Daisuke ISHIMARU; Fukuto NAGATA (Nihon Kikai Gakkai ronbunshu, 2015)
Near-dry cutting is a key technology to decrease in the usage of cutting fluid. A lot of research achievements revealed that near-dry cutting technology was available, and we hope this technology will contribute to the improvement of the working environment in the manufacturing industry. On the other hand, a large diameter deep hole drilling process still needs a large amount of cutting fluid. This paper describes the results of feasibility study on deep hole counter boring with a BTA(Boring and Trepanning Association) tool using near-dry technology. In the experiments, the work material was JIS A2017 aluminum alloy and JIS S35C carbon steel. Their workpiece has a prepared hole with various diameters. The workpiece temperature increase was recorded during drilling, and the maximum height roughness on inner wall of hole was measured with a surface roughness measuring instrument by stylus method. The cutting lubricant supply system affected the chip discharging efficiency and the temperature rise of workpiece. As a result, the difference of supply method affected the roughness on inner wall of hole. The results of this experiment revealed the following things. In the case of a deep hole machining of an aluminum alloy, the wet method is more excellent in surface roughness than the method using MQL. On the other hand, MQL is effective for drilling of a carbon steel. And furthermore, the fundamental guidelines of the diameter and position of oil hole was revealed with the object of putting near-dry deep hole drilling to practical use in the future.